SUKUK AS AN ALTERNATIVE FINANCING FOR REGIONAL BUDGET (APBD) TOWARD THE DEVELOPMENT OF REGIONAL DRINKING WATER INFRASTRUCTURE - Nurul Azizah; Hendri Tanjung; Mukhamad Yasid (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2022)
Purpose–The aim of the study is trying to explorethe potential alternatives financing scheme for infrastructure development on the supply system of drinking water (SPAM –Sistem Penyediaan Air Minum) in Perumda Tirta Pakuan Kota Bogor through the issuance Sukuk. Design/methodology/approach–To achieve this objective, the current study used the following methodology Analytical Network Process (ANP), conducted using an in-depth interview with nine interviewees who considered knows the problems in investment financing for development of infrastructure in drinking water sector. They are from the government, academics, private sector, finance and business players. Findings–. The results show that most respondents in the alternative financing cluster choose Project-Based Sukuk (PBS) as a priority at 27.17%, followed by Corporate Sukuk at 25.66%; Hybrid Sukuk is 16.96%; and Municipal Sukuk is 15.96%. Research limitations/Implications–This study has a research limitations is alternative financing that focuses on the type of sukuk that can be used as an alternative to regional budget (APBD)financing for development of regional drinking water infrastructure.The government is looking for appropriate financing alternatives for the development of drinking water infrastructure for continuously the availability of water. Originality/value–This adds to the scarce literature of alternative financing for regional budget (APBD) toward the development of drinking water infrastructure. The study contributes the literature on the problem of limited corporate funds to develop the infrastructure of drinking water and this research provides alternative financing through Sukuk. Keywords-Sukuk, ShariaFinancial Instruments, Analytical Network Process (ANP)